Population Structure of Mangrove Snails (Terebralia sulcata) Around the Nickel Mining Area of Pomalaa, Southeast Sulawesi - Muhammad Fajar Purnama; Farid Yasidi; Dedy Oetama; Haslianti Haslianti; Salwiyah Salwiyah; La Ode Abdul Rajab Nadia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Nickel mining in Pomalaa, Southeast Sulawesi, potentially alters mangrove ecological dynamics, specifically affecting benthic biota. This study analyzes the population structure of the mangrove snail (Terebralia sulcata) using purposive systematic sampling across reference, transition, and mining-impacted zones. Data were collected via transect quadrat methods (5x5 m²) during January 2024–January 2025. Water quality analysis indicated significant elevations in dissolved Ni and organic loads (COD/BOD) in impacted areas. Population structure revealed a unimodal distribution dominated by the 35–45 mm class, with limited juvenile recruitment in stressed sites. The length-weight relationship (LWR) exhibited a strong negative allometric pattern (b = 2.02), indicating faster shell length growth as an adaptive response to environmental stressors. Despite a stable condition factor (Kn = 1.124), spatial disparities were evident through a progressive decline in density and biomass toward impacted stations. This study provides a significant scientific contribution by establishing T. sulcata as a sensitive bioindicator for nickel pollution. The findings emphasize that mining-derived stressors negatively correlate with biological performance, highlighting the necessity for policy-driven bioindicator monitoring and the integration of benthic health assessments into coastal management protocols within nickel industrial zones to mitigate long-term ecological degradation.